2006
DOI: 10.1080/00480169.2006.36693
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-pathological findings in cattle exposed to chronic bracken fern toxicity

Abstract: Monocytosis, detected in 31% of the younger animals, could represent an initial response to consumption of bracken fern and might be useful as an early haematological marker of BEH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Studies show that tumors of the urinary bladder in cattle are of epithelial and mesenchymal origin and are commonly associated with chronic enzootic hematuria, a syndrome caused by prolonged ingestion of bracken fern (21,22). In line with this, the postmortem examination of all the affected animals in the present study showed multiple tumors in the urinary bladder wall, which were either pedunculated or broad with marked areas of bleeding; moreover, histologically, hemangiosarcoma and hemorrhages were observed in the mesenchymal part of the bladder, revealing the presence of tumors (7).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Studies show that tumors of the urinary bladder in cattle are of epithelial and mesenchymal origin and are commonly associated with chronic enzootic hematuria, a syndrome caused by prolonged ingestion of bracken fern (21,22). In line with this, the postmortem examination of all the affected animals in the present study showed multiple tumors in the urinary bladder wall, which were either pedunculated or broad with marked areas of bleeding; moreover, histologically, hemangiosarcoma and hemorrhages were observed in the mesenchymal part of the bladder, revealing the presence of tumors (7).…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, tumors can develop in the gastrointestinal tract. Chronic enzootic hematuria is the most common type of bracken fern poisoning in cattle and is characterized by intermittent hematuria and anemia and other signs, such as acute hemorrhagic syndrome, hemorrhagic diathesis, and upper gastrointestinal tract neoplasia (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Fletcher and co-workers mentioned above the plasma activity of AST, creatine kinase, GD and GGT were reported to be within reference values and no histological changes were found in the liver. The enzyme levels in cattle with chronic ingestion of bracken are also varying between studies [43,44]. The differences may be related to the different composition and concentration of other compounds present in bracken [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…In monogastric (single-stomach) animals, such as horses, toxicity is related to the enzyme thiaminase (Perez-Alenza et al, 2006;Vetter, 2009;Di Loria et al, 2012). In horses, thiaminase breaks into the necessary vitamin thiamine (B1), pyrimidine, and thiazole, which are inactivated in body (Knight and Walter, 2001).…”
Section: Thiamine Deficiency In Monogastricsmentioning
confidence: 99%
“…It is a lactone molecule discovered in highest concentrations in young growing parts of the plant (Perez-Alenza et al, 2006;Di Loria et al, 2012;Panter et al, 2011).…”
Section: Acute Hemorrhagic Syndrome (Loss Of Blood)mentioning
confidence: 99%